Ultrasonication to inactivate the proteolytic enzymes in suni bug-damaged wheat. (September 2016) - Durak, Atike Nur; Erbaş, Mustafa; Arslan, Sultan
Abstract: In this study, the possibility of using ultrasonic waves for different time periods at different power levels to inactivate proteolytic enzymes in wheat kernels originated from bug-damage was investigated. For this aim, sound wheat as the control sample and wheat samples containing 3% (w/w) bug-damaged wheat were sonicated in water (1:2) for different time periods (0, 4, 8 and 12 min) at different power levels (25%, 50%, 75% and 100% of 96 W) and with 10-second-on-5-second-off pulses. The samples with 3% bug damaged wheat showed significant difference compared to sound samples. There was a significant increase in modified sedimentation values, wet and dry gluten contents of the samples depending on increasing sonication time. Total free amino acid, and free proline contents of the samples also showed significant decrease depending on sonication time. But different power level of sonication does not have any significant effects on any result. Consequently, ultrasonic treatment has a statistically significant effect on decreasing the proteolytic activity of bug-damaged wheat while it does not affect the quality of the sound wheat. Highlights: Ultrasonication applied to bug-damaged wheat kernels. The effects of sonication on bug originated proteolytic enzymes were investigated. Partial inactivation of proteolytic enzymes was done depending on sonication time. Sonication has no negative effects on technical quality and structure of wheat.